Assessment of Achievement and Socio-Economic Status of Power Lifters of Jammu Region (International Journal of Food and Nutritional Sciences, 2022)
Objective: The present study is to assess the socio-economic status and achievement of power-lifters of Jammu region.Method used:15 males and 15 females power lifters between the age of 20-45yrs, matriculate or above were selected comprising a sample size of (n=30). To access social economic status ,modified Kuppuswamy scale was used. Further, achievement of power lifters was assessed through closed ended questionnaire. Findings: It has been concluded that socio economic status of family does plays a major role in achievement of power lifters. Males get more socio-economic support from family than girls. Most of the athletes belong to high class families having income more than Rs47,500 per month and the power lifters who got mental and physical support tends to perform better rather than those doesn’t having any mental and physical support.Application: This study recommends parents/ guardians to provide both financial and mental support to their wards so that they should be able to represent themselves at international level and improve their performance.